Automotive embedded systems handbook - Navet, Nicolas; Simonot-Lion, Françoise (Industrial information technology series., 2009)
Providing an outline of methods for designing and implementing automotive systems, this handbook presents an overview of automotive electronic systems. It highlights the technical requirements of in-vehicle architectures, the multipartner development process, software engineering methods, and embedded communications.